2013
DOI: 10.1371/journal.pone.0077534
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Bax Promoter (-248G>A) Single Nucleotide Polymorphism and Susceptibility towards Cancer: Evidence from a Meta-Analysis

Abstract: BackgroundThe Bcl-2-associated X protein (Bax) is a proapoptotic member of the Bcl-2 family known to be activated and upregulated during apoptosis. Single nucleotide polymorphisms (SNPs) in Bax promoter may participate in the process of carcinogenesis by altering its own expression and the cancer related genes. Bax-248G>A polymorphism has been implicated to alter the risk of cancer, but the listed results are inconsistent and inconclusive. In the present study, we performed a meta-analysis to systematically su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Our study did not find an association between BAX 2248G > A polymorphism and the risk of chromosomal damage induced by VC, although the BAX 2248G > A variant heterozygote were at lower risk of chromosomal damage compared with the wild-type genotype (FR 5 0.82, 95%CI: 0.64-1.03, P 5 0.0964; adjusted FR 5 0.81, 95%CI: 0.63-1.03, P 5 0.0941, adjusted for age, gender, smoking status and alcohol consumption status), which did not reach statistical significance. Recently, a meta-analysis confirmed our results and revealed that the BAX-248G > A polymorphism might be not an important risk factor in the process of carcinogenesis [Sahu and Choudhuri, 2013]. Nevertheless, additional researches with larger size of samples are required to validate the association of this polymorphism with the risk of cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Our study did not find an association between BAX 2248G > A polymorphism and the risk of chromosomal damage induced by VC, although the BAX 2248G > A variant heterozygote were at lower risk of chromosomal damage compared with the wild-type genotype (FR 5 0.82, 95%CI: 0.64-1.03, P 5 0.0964; adjusted FR 5 0.81, 95%CI: 0.63-1.03, P 5 0.0941, adjusted for age, gender, smoking status and alcohol consumption status), which did not reach statistical significance. Recently, a meta-analysis confirmed our results and revealed that the BAX-248G > A polymorphism might be not an important risk factor in the process of carcinogenesis [Sahu and Choudhuri, 2013]. Nevertheless, additional researches with larger size of samples are required to validate the association of this polymorphism with the risk of cancer.…”
Section: Discussionsupporting
confidence: 74%
“…In mitochondria-mediated apoptotic cell death process,Bax activation irreversibly leads to cell death. The Bax promoter contains response elements for an important tumor suppressor, p53, and this affects gene expression ( 9 ).The Bcl-2 gene, a proto-oncogene that blocks apoptosis, was identified at the chromosomal breakpoint of t( 14 ; 18 ) bearing B-cell lymphomas. Its gene product is an anti-apoptotic molecule that modulates the mitochondrial release of cytochrome c, and the interaction of apoptosis activating factors with caspase 9 and Bax (Bcl-2 associated × protein).…”
Section: Discussionmentioning
confidence: 99%
“…BAX was extensively studied in different types of cancer such as pancreatic cancer 45 , colon cancer 46 47 , esophageal cancer 48 , lung cancer 49 50 , squamous cell carcinoma of the head and neck 11 , prostate carcinoma 51 , ovarian carcinoma 52 , and breast cancer 53 . Recently, BAX-248G>A (rs4645878) was reported to be associated with reduced expression of BAX protein and altered susceptibility to chronic lymphocytic leukemia 25 26 , although a meta-analysis of seven independent studies with 1772 cases and 1708 controls revealed that neither allele frequency nor genotype of BAX-248G>A associated with risk of human cancer using different genetic models 54 . Several studies reported that patients with BAX low expression had a significantly longer median survival in NSCLC 50 , esophageal squamous cell carcinoma 48 , and colon cancer 47 .…”
Section: Discussionmentioning
confidence: 99%